Ethnochemistry In Chemistry Learning: Insights from Indonesian Local Wisdom - Junaidi, Eka; Sudatha, I Gde Wawan; Suartama, I Kadek; Santosa, Made Hery (Jurnal Pendidikan MIPA, 2025)
This study aims to analyze the role of ethnochemistry as an innovative approach in chemistry education by examining its impact and development strategies based on local wisdom. Ethnochemistry combines cultural practices with chemical concepts to create meaningful and inclusive learning. This study focuses on the impact of ethnochemistry on chemistry learning and its development strategies to support inclusive and multicultural chemistry education. These findings are expected to enrich culturally relevant chemistry education and support the preservation of cultural heritage. This study employed the Systematic Literature Review (SLR) method, adhering to the PRISMA protocol to ensure transparency and repeatability. The initial search was conducted in Scopus, Google Scholar, Semantic Scholar, and Crossref, using the keyword "ethnochemistry." From a total of 225 articles, 27 articles were selected that met the inclusion criteria in the form of publications from 2020-2025. Articles must contain the keyword ethnochemistry or "ethnochemistry" in the title, must not be articles published in proceedings or repositories, must not duplicate articles with the same title, and must be indexed by Scopus or articles accredited by Sinta 1 and 2. The results showed that ethnochemistry significantly improved students' conceptual understanding, 21st-century skills (such as critical and creative thinking), and motivation. This approach also strengthens cultural preservation by connecting chemical concepts and local cultural practices. The main strategies for its development include: (1) Technology-based teaching materials (e.g., AR/VR, Adobe Flash), (2) Contextual learning approaches (e.g., PBL and CRT), (3) Collaboration with local communities, and (4) Expansion of research on underrepresented cultures. It can thus be concluded that ethnochemistry not only enhances the appeal and relevance of chemistry learning but also plays an important role in preserving cultural heritage. To optimize its potential, comprehensive strategies are necessary, including integrating ethnochemistry into the national curriculum, increasing teacher capacity through training, and utilizing digital technologies. Further research is also needed to evaluate the long-term impact and expand its application to various cultural contexts. This approach ensures inclusive, sustainable, and globally relevant chemistry education.    Keywords: ethnochemistry, local wisdom, education, inclusive, systematic review.